Grammatical relations in Ikalanga - Joyce T. Mathangwane (LibraryPress@UF, 2006)
Although facts about grammatical relations in many Bantu languages have been established since the early 1970s, there are still languages in this family which have not benefited from such studies. One of these is Ikalanga, spoken in Botswana and Zimbabwe. This paper examines the core grammatical relations of Ikalanga, exploring its typological status in terms of double object constructions. In prototypical ditransitive constructions, the Recipient NP has all of the properties of Direct Object, whereas the Theme NP has only some of those features. The conclusion is that Ikalanga is an intermediate language if object symmetricity is scalar. However, it is shown that in marked applicative constructions where the Benefactive is non-human and the Theme is human, there is reason to argue for 'split direct-objecthood', reflecting the impact of animacy in the assignment of direct objecthood.